Vers une lubrification sèche pour le patrimoine horloger - Emilie Cornet (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Compared to a traditional lubrication, a solid lubricant coating brings significant benefits such as stability and surface’s protection, and requires no maintenance. The coatings chosen for this study are a three-component ceramic called TiSiC and an amorphous carbon coating, both deposited by PVD. They have been tested and optimised by tribological pin-on-disk test and a horological ageing test on modern watch mechanisms. These coatings are consistent with the specific needs of heritage: reversibility and safety for the object.